Effects of Shrinkage Reducing Agent and Expansive Additive on Mortar Properties - Sarapon Treesuwan; Komsan Maleesee (Advances in Materials Science and Engineering)
This research is to study the effect of mortar mixed with shrinkage reducing agent (polyoxyalkylene alkyl ether type), expansive additive (CaO type), and fly ash (hereinafter “SRA,” “EX,” and “FA,” resp.). Moreover, steam curing was studied to improve the properties of mortar. The plastic shrinkage test was conducted by using the strain gauge embedded at 0.5 cm from the surface according to the ASTM C1579-06 standard within early age followed by the total shrinkage test and compressive strength test. The test results showed that mixing both the EX and SRA increases the plastic enlargement of the mortar during the early age more than using either the EX or SRA solely. The steam curing helps to reduce the plastic shrinkage when the mortar is added with the FA and SRA while adding the EX increases the enlargement compared to the normal curing. When the EX, SRA, and FA are all added to the mortar mixing, great attention should be paid due to the increase of greater enlargement. For the compressive strength view, the steam curing increases the compressive strength in all types of mixture. The steam curing significantly helps increasing the compressive strength of mortar with combination of EX, SRA, and FA. Nevertheless, the XRD and SEM tests explain such enlargement accordingly.